Effects of light source on the performance of a Kretschmann surface plasmon resonance sensor. (20th May 2016) - Liu, Sha; Li, Min; Gong, Chaoyang; Gao, Hongyun
Abstract: The effects of light source are usually neglected in most surface plasmon resonance sensors for indoor operations. However they should not be ignored in high precision applications. This paper further analyzes the light source parameters, including peak wavelength, divergence angle and spectral linewidth, by using a modified Gauss distribution assumption in a Kretschmann configuration surface plasmon resonance sensor. A light beam with a specific divergence angle or linewidth can be expressed as the superposition of lights with a range of adjacent incident angles or continuous monochromatic lights. Theoretical modelling and calculation show that an increase of wavelength reduces resonance angle. Both light beam divergence angle and spectral linewidth are proportional to the shift of resonance angle. Our experiments accordingly demonstrate that the change of wavelength from 632.8 nm to 852.4 nm cause a 1.51° decrease in the resonance angle, and a divergence angle increment of 3.9° leads to about 1.21° increment in the resonance angle.